Hubungan Antara Pengetahuan Ibu Dengan Pemberian Imunisasi Dasar Pada Bayi Di Puskesmas Jetis Kota Yogyakarta - Ginu, Nestaria Kaharina Ngete; Febriani, Hehi; Ernawati, Yuli (Jurnal Kesehatan Masyarakat, 2015)
ABSTRACT UNICEF says there are 2,400 children in Indonesia die every day, including who died of tuberculosis, measles, pertussis, diphtheria, and tetanus. Diseases that can be prevented by immunization is a contagious disease that is potentially causing outbreaks and mortality, especially for infants. The study aims to know the relationship between the mothers knowledge base for infant immunization in the health center Jetis Yogyakarta. This type of research is quantitative descriptive cross-sectional approach. The population of this study mothers with babies who come to immunization with a total sample of 92 taken by accidental. Collecting data using questionnaires. Data analysis using the Spearman rank test significance level of 0.005. Results Spearman rank of 0.643 (? = 0.000). Mothers level of knowledge in the low category of 7.6%, quite as much as 81.5%, and 10.9% as much either. Immunization complete or not as much as 91.3% and 8.7% immunization. There is a relationship between the mothers knowledge of basic immunization given to infants in the health center of Yogyakarta City Jetis.